2003
DOI: 10.1359/jbmr.2003.18.1.58
|View full text |Cite
|
Sign up to set email alerts
|

A Short Pulse of Mechanical Force Induces Gene Expression and Growth in MC3T3-E1 Osteoblasts via an ERK 1/2 Pathway

Abstract: Physiological mechanical loading is crucial for maintenance of bone integrity and architecture. We have calculated the strain caused by gravity stress on osteoblasts and found that 4 -30g corresponds to physiological levels of 40 -300 strain. Short-term gravity loading (15 minutes) induced a 15-fold increase in expression of growth-related immediate early gene c-fos, a 5-fold increase in egr-1, and a 3-fold increase in autocrine bFGF. The non-growth-related genes EP-1, TGF-␤, and 18s were unaffected by gravity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
110
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(123 citation statements)
references
References 43 publications
10
110
3
Order By: Relevance
“…Interestingly, Jessop et al found that ERK activation patterns differed between both stimuli (15). In addition, centrifugation, which has also been used as a mechanical stimulus in vitro, did induce ERK activation in MC3T3 cells; however, FAK phosphorylation did not occur in this model (13), whereas it was observed in our work. Altogether, these data demonstrate that, whereas various stimuli appear to be relevant in terms of bone physiology, they are not redundant in terms of molecular events Moreover, the type and stage of differentiation also modulate mechanically induced ERK acti- vation.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Interestingly, Jessop et al found that ERK activation patterns differed between both stimuli (15). In addition, centrifugation, which has also been used as a mechanical stimulus in vitro, did induce ERK activation in MC3T3 cells; however, FAK phosphorylation did not occur in this model (13), whereas it was observed in our work. Altogether, these data demonstrate that, whereas various stimuli appear to be relevant in terms of bone physiology, they are not redundant in terms of molecular events Moreover, the type and stage of differentiation also modulate mechanically induced ERK acti- vation.…”
Section: Discussioncontrasting
confidence: 86%
“…Recent reports demonstrated that mechanical strain is able to activate ERK1/2 in several adherent cells such as mesangial cells (6), smooth muscle cells (7), and chondrocytes (8). In osteoblasts, ERK activation was mostly reported in fluid flow (9 -12), centrifugation (13), or magnetic drag force (14) experiments and in only one study using cyclic stretch (albeit combined with fluid flow) (15). However, cell stretch appears to be a relevant model of mechanical stimulus in the bone field (16,17) and provides specific osteoblastic responses (18).…”
mentioning
confidence: 99%
“…Many studies have shown that effective physical stimulation could induce a series of biological changes in osteoblasts, such as osteogenic effect (58,59), alteration of gene expression (44,60), and related signal pathway changes (44,61). The beneficial effects for enhanced osteoblast adhesion and migration may result from reorganization of actin cytoskeleton to a certain degree (23).…”
Section: Journal Of Biological Chemistry 26207mentioning
confidence: 99%
“…Although physical processes, and therefore biological systems, are behaving differently under (near) weightlessness (Albrecht-Buehler 1991;Todd 1989;van Loon 2007c) including studies under hypergravity c.q. hyper-weight conditions provide information for the entire gravity spectrum (Hatton et al 2003;Hemmersbach and Haeder 1999;Thoumine et al 1996;Searby et al 2005;Tabony 2004;van Loon et al 1999). It was at first argued from a purely physical point of view, that non-specialized single cells might not be susceptible to small forces such as gravity (Pollard 1965;Went 1968), many studies have shown otherwise.…”
Section: Instruments and Methods To Study (Sub-) Cellular And Moleculmentioning
confidence: 99%